Kesehatan dan Keselamatan Kerja bagi Petugas Kebersihan di Dinas Kehutanan dan Lingkungan Hidup Provinsi Bali - Kadek Yohanes Septianadi; I Nyoman Gedesugjartha; I Putu Gede Seputra (Jurnal Interpretasi Hukum, 2021)
The risk from environmental cleaners is very high considering the work they do, where their work is always related to cleaning the garbage that is within the Bali Provincial Forestry and Environment Service. In this regard, the purpose of this study is to reveal the health and safety insurance for cleaners in the Bali provincial forestry office and the government 's legal protection on guaranteeing the implementation of occupational health and safety for cleaners at the Bali Provincial Forestry and Environment Service. This research method is empirical legal research. Primary data is obtained through field research, secondary data is obtained from books, laws and regulations. The legal materials obtained are then classified and combined as well as analyzed systematically and presented descriptively. This study concludes that the regulation regarding health insurance for workers in the Bali Provincial Forestry Service is in accordance with the regulations stipulated by Law no. 13 Year 2003.